Device conformability and morphological assessment after TEVAR for aortic type B dissection: a single-centre experience with a conformable thoracic stent-graft design - Bischoff, Moritz; Müller-Eschner, Matthias; Meisenbacher, Katrin; Peters, Andreas; Böckler, Dittmar (Medical science monitor. Basic research, 2015)
BACKGROUND - The aim of this study was to analyze device conformability in TEVAR of acute and chronic (a/c) type B aortic dissections (TBAD) using the Gore Conformable Thoracic Aortic Stent-graft (CTAG). - MATERIAL AND METHODS - From January 1997 to February 2014, a total of 90 out of 405 patients in our center received TEVAR for TBAD. Since November 2009, 23 patients (16 men; median age: 62 years) were treated with the CTAG. Indications were complicated aTBAD in 15 (65%) and expanding cTBAD in 8 (35%) patients. Primary endpoints were the assessment of device conformability by measuring the distance (D) from the radiopaque gold band marker (GM) at the proximal CTAG end to the inner curvature (IC) of the arch on parasagittal multiplanar reformations of CT angiography, as well as the evaluation of aortic diameter changes following TEVAR. Median follow-up was 13.3 months (range: 2 days to 35 months). - RESULTS - Primary and secondary success rates were 91.3% (21/23) and 95.6% (22/23), respectively. There was 1 type Ia endoleak, retrograde dissection or primary conversion was not observed. Median GM-IC-D was 0 mm (range: 0 mm to 10 mm). GM-IC-D was associated with zone 2 placement compared to zone 3 (P=0.036). There was no association between GM-IC-D formation and arch type. In aTBAD cases the true lumen significantly increased after TEVAR (P=0.017) and the false lumen underwent shrinkage (P=0.025). In cTBAD patients the false lumen decreased after TEVAR (P=0.036). - CONCLUSIONS - The CTAG shows favorable conformability and wall apposition in challenging arch pathologies such as TBAD.
Gesehen am 26.05.2020